The first complete mitochondrial genome of Curcuma amarissima (Zingiberaceae): insights into multi-branch structure, codon usage, and phylogenetic evolution - Heng Liang; Jiabin Deng; Yidan Wang; Gang Gao; Ruiwu Yang (BMC Genomics)
Abstract Background As a key genus in Zingiberaceae, Curcuma is widely studied for its taxonomic diversity, the presence of bioactive curcuminoids and volatile oils, and its extensive applications in traditional medicine and economic products such as spices and cosmetics. Although chloroplast genomes have been assembled and published for over 20 Curcuma species, mitochondrial genomic data remain limited. Results We successfully sequenced, assembled, and annotated the mitogenome of Curcuma amarissima (C. amarissima) using both Illumina short reads and Nanopore long reads, achieving the first complete mitogenome characterization in the Zingiberaceae family. The C. amarissima mitogenome features a unique multi-branched structure, spanning 6,505,655 bp and consisting of 39 distinct segments. It contains a total of 43 protein-coding genes, 63 tRNA genes, and 4 rRNA genes, with a GC content of 44.04%. Codon usage analysis indicated a weak bias, with neutrality plot analysis suggesting natural selection as a key factor shaping mitochondrial codon usage in C. amarissima. The mitogenome provides valuable insights into genome size, coding genes, structural features, RNA editing, repetitive sequences, and sequence migration, enhancing our understanding of the evolution and molecular biology of multi-branched mitochondria in Zingiberaceae. The high frequency of repeat sequences may contribute to the structural stability of the mitochondria. Comparing chloroplast genome, phylogenetic analysis based on the mitochondrial genome establishes a foundation for further exploration of evolutionary relationships within Zingiberaceae. Conclusions In short, the mitochondrial genome characterized here advances our understanding of multi-branched mitogenome organization in Zingiberaceae and offers useful genomic resources that may support future breeding, germplasm conservation, and phylogenetic studies, though further research is necessary.